IMF Survey, Volume 32, Issue 02. (IMF Survey; IMF Survey, 2003)
Anoop Singh, a national of India, took charge of the IMF's Western Hemisphere Department in September 2002. Before that, he was Director for Special Operations-a unit formed in 2002 to bring together the IMF's expertise in resolving financial crises. In both positions, he has drawn on his over 25 years of experience at the IMF-as Deputy Director of the departments covering the Asia-Pacific region in the mid- to late 1990s, including during the Asian financial crisis and its aftermath. In the early 1980s, he served as Special Advisor to the Governor of the Reserve Bank of India. Laura Wallace spoke with Singh about the challenges the department faces, especially in the IMF's efforts to end the financial crises in Latin America and rebuild growth.